EFFECTIVENESS OF THE LARVACIDE ETHANOL EXTRACT OF JACKFRUIT (Artocarpus heterophyllus L.) AGAINST Aedes aegypti LARVA - Selvi Marcellia; Rediyanto; Dewi Chusniasih (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights Jackfruit leaf extraction was performed by percolation method using 96% ethanol solvent with flavonoid, saponin, tannin, alkaloid, and steroid terpenoid test. Jackfruit leaf extract was effective as a larvicide against larvae of Aedes aegypti. Abstract Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus, which enters the human bloodstream through the bite of a mosquito of the Aedes genus. The DHF control program is carried out by breaking the vector chain, the Aedes aegypti larvae. The underutilized jackfruit (Artocarpus heterophyllus L.) leaves contain secondary metabolites that have the potential to be larvicides. Secondary metabolites that have the potential as larvicides are flavonoids, saponins, tannins, alkaloids, steroids, and terpenoids. Objective: This study was to determine the effectiveness of jackfruit leaf extract as a larvicide in controlling Aedes aegypti vectors and to determine the most effective concentration of jackfruit leaf extract as an Aedes aegypti larvicide. Material and Method: The study was an analytic observational study using a cross-sectional design. The study was conducted from March 2022 to April 2022. Jackfruit leaf extraction was performed by percolation method using 96% ethanol solvent with flavonoid, saponin, tannin, alkaloid, and steroid terpenoid test. The data were analyzed with SPSS Anova (parametric) and Kruskal Wallis non-parametric. Result: In the extraction of 243 gr jackfruit leaves using the percolation method, the yield was 24.3%. Jackfruit leaf extract was effective as a larvicide against Aedes aegypti larvae, even at a concentration of 0.75%. The LC50 results for the total concentration obtained were 0.331% with strong toxicity (poisonous). Jackfruit leaf extract at a concentration of 2% yielded mortality value of 91.2 at 8 hours and at a concentration of 3% it yielded mortality value of 96 at 8 hours. Conclusion: Jackfruit leaf extract was effective as a larvicide against Aedes aegypti mosquito larvae.